2010
DOI: 10.3354/meps08481
|View full text |Cite
|
Sign up to set email alerts
|

Past and present grazing boosts the photo-autotrophic biomass of biofilms

Abstract: Little is known about the long-term consequences of grazing effects on microphytes. This study tested density-dependent responses to grazer removal on the biomass (chlorophyll a, chl a) and composition of natural high rocky-shore biofilms over a 7 mo period. Gastropod snails Melarhaphe neritoides graze entirely within circular halos generated in biofilms surrounding their refuges. The experiment crossed 3 levels of original snail density per halo with 3 levels of grazing intensity (generated by 100, 50 and 0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…In the system investigated in this study, small-scale topographic features, such as pits and crevices, could have provided more favorable habitats for EMPB during high desiccation stress, thus promoting heterogeneity in biomass distribution more during the warm months than the cold months. In addition, topography might have mediated the impact of biotic interactions, in particular, the grazing pressure exerted on biofilm by the littorinid snail Melaraphe neritoides (Stafford & Davies 2005, Skov et al 2010, Dal Bello et al 2015). An increase in spatial variance of microphytobenthos at small scales has been related to grazing activity both on rocky shores and in soft sediments (Stafford & Davies 2005, Como et al 2014.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the system investigated in this study, small-scale topographic features, such as pits and crevices, could have provided more favorable habitats for EMPB during high desiccation stress, thus promoting heterogeneity in biomass distribution more during the warm months than the cold months. In addition, topography might have mediated the impact of biotic interactions, in particular, the grazing pressure exerted on biofilm by the littorinid snail Melaraphe neritoides (Stafford & Davies 2005, Skov et al 2010, Dal Bello et al 2015). An increase in spatial variance of microphytobenthos at small scales has been related to grazing activity both on rocky shores and in soft sediments (Stafford & Davies 2005, Como et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Underwood 1978, Christofoletti et al 2011, Sanz-L谩zaro et al 2015 and facilitates the settlement of algal propagules and invertebrate larvae (O'Connor & Richardson 1998, Huang & Hadfield 2003. In addition, relatively recent studies have shown that some invertebrates (namely littorinids and barnacles) can in turn positively affect EMPB biomass through facilitation mechanisms (Skov et al 2010, suggesting that interaction webs involving EMPB are complex. Deepening our knowledge of spatio-temporal variability of these organisms is an important and rarely accomplished step toward the identification of factors affecting major primary producers of rocky shore habitats.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that although herbivore effects were traditionally assumed to be negative (Lubchenco & Gaines 1981), some recent studies confirmed that grazers may also exert facilitative effects on their prey, for example by removing a biofilm鈭抎etritus complex and facilitating light and nutrient penetration (Underwood & Murphy 2008, Skov et al 2010). In addition, excretion of limiting resources may fertilize MPB assemblages (Plag谩nyi & Branch 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The halo area increases linearly with snail density per refuge (Skov et al 2010). Halos contract in winter when the biofilm food is rich (Thompson et al 2004) and expand in spring with reducing biofilm biomass, becoming less visible during the summer lull in biofilm productivity (Skov et al 2010). Melarhaphe neritoides rarely move outside the grazing halo, although they can travel 20 cm h 脌1 (Stafford and Davies 2005).…”
Section: Conceptual Modelmentioning
confidence: 99%
“…It was estimated using Color Infra-Red photography (CIR; Murphy et al 2006), with methods detailed fully in Skov et al (2010). A CIR camera was mounted in an aluminum frame to produce images of the 50 3 50 cm plot centers.…”
Section: Response Variablesmentioning
confidence: 99%